A novel FAM83H mutation in one Chinese family with autosomal-dominant hypocalcification amelogenesis imperfecta. (24th September 2018) - Yu, Shunlan; Quan, Junkang; Wang, Xiaozhe; Sun, Xiangyu; Zhang, Xianli; Liu, Yang; Zhang, Chenying; Zheng, Shuguo
Abstract: Autosomal-dominant hypocalcification amelogenesis imperfecta (ADHCAI) is characterized by soft enamel that easily disintegrates and exposed dark dentin. ADHCAI is caused by mutations in a gene called family with sequence similarity 83 member H ( FAM83H ). To investigate the molecular genetics of ADHCAI, a Chinese family in which three generations exhibited ADHCAI was recruited. The enamel ultrastructure was analysed by environmental scanning electron microscopy (ESEM), which showed altered enamel rod (prism) structures in ADHCAI patients compared to the structures in healthy controls. Mutational analysis of the FAM83H gene identified a novel nonsense mutation (c.1222A>T) in the affected family members that encodes a stop codon at amino acid position 408, causing premature protein truncation (p. K408X). Green fluorescent protein (GFP) and FAM83H fusion protein analyses in vitro showed that normal cytoplasmic accumulation of the FAM83H protein was prevented by the K408X mutation in both rat dental epithelial SF2 cells and human embryonic kidney 293T cells. The mutant fusion protein localized primarily to the nucleus, in contrast to the cytoplasmic subcellular localization of the wild-type FAM83H protein. Our results provide new genetic evidence that mutations in FAM83H contribute to ADHCAI.